Alexithymia in Parkinson's disease: a point of view on current evidence. (June 2016) - Costa, Alberto; Caltagirone, Carlo
The risk of alexithymia in individuals with Parkinson's disease (PD) is about double compared with that observed in the general population. This finding indicates that alexithymia may be a relevant phenomenon in PD. However, several issues have to be clarified. The review here proposed outlines two main points. First, available data do not allow the clarification of whether alexithymia is independently associated with PD or if it is secondary to other mood and/or cognitive disorders. Second, it is not well understood how PD-related neurobiological changes may account for alexithymic expression. Our examination of extant literature also evidenced some potential limits of current tools and designs used that should carefully taken into account in further investigations of above issues.